2009
DOI: 10.1073/pnas.0907357106
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α inhibition promotes p53 pathway activity, tumor cell death, and radiation responses

Abstract: Approximately 50% of cancer patients receive radiation treatment, either alone or in combination with other therapies. Tumor hypoxia has long been associated with resistance to radiation therapy. Moreover, the expression of hypoxia inducible factors HIF1␣ and/or HIF2␣ correlates with poor prognosis in many tumors. Recent evidence indicates that HIF1␣ expression can enhance radiation-induced apoptosis in cancer cells. We demonstrate here that HIF2␣ inhibition promotes tumor cell death and, in contrast to HIF1␣,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
164
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 31 publications
11
164
0
3
Order By: Relevance
“…24 Since tumor VN is also characterized by a loss of hypoxia (and a return to normoxia) within the TME, 24,25 we analyzed treated vs. control tumors for expression of the hypoxiaassociated biomarker HIF-2a. [25][26][27] We determined that tumors in mice vaccinated with lvDLK1 or (more so) lvDLK1 C lvDLK2 displayed significant reductions in HIF-2a transcript levels vs. control-untreated tumors (Fig. 3D), consistent with therapeutic VN in these treatment cohorts.…”
Section: Resultssupporting
confidence: 52%
“…24 Since tumor VN is also characterized by a loss of hypoxia (and a return to normoxia) within the TME, 24,25 we analyzed treated vs. control tumors for expression of the hypoxiaassociated biomarker HIF-2a. [25][26][27] We determined that tumors in mice vaccinated with lvDLK1 or (more so) lvDLK1 C lvDLK2 displayed significant reductions in HIF-2a transcript levels vs. control-untreated tumors (Fig. 3D), consistent with therapeutic VN in these treatment cohorts.…”
Section: Resultssupporting
confidence: 52%
“…The fact that Hif2a itself is regulated by ROS may indicate a role as a primary sensor of oxidative stress. In support, ROS accumulation and improved response to radiation therapy by HIF2A inhibition was recently described in human tumor cells (Bertout et al 2009). These findings may implicate a role for HIF2A in radiation and chemotherapy resistance in tumor and possibly normal stem cells.…”
Section: Phenotypic Effects Of Hif-2α Eliminationmentioning
confidence: 64%
“…19,40 We propose that this transient HIF-1a stabilisation represents an adaptive response to the low O 2 , whereas HIF-2a maintains a physiological response. 19 This later appearance and persistence of HIF-2a may also contribute to the increased numbers of NPCs generated at 3% O 2 : HIF-2a inhibits the p53 pathway and also regulates SOD1, SOD2, GPX1 and CATALASE expression, 41 so is well placed to modulate the survival of NPCs. Moreover, HIF-2a appears to have a critical role in the proliferation of neuroblastoma cells, 41 and the ability of our system to isolate the downstream effects of HIF-2a from HIF-1a could provide further insights into this observation, as well as into the mechanisms of maintenance of endogenous NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…19 This later appearance and persistence of HIF-2a may also contribute to the increased numbers of NPCs generated at 3% O 2 : HIF-2a inhibits the p53 pathway and also regulates SOD1, SOD2, GPX1 and CATALASE expression, 41 so is well placed to modulate the survival of NPCs. Moreover, HIF-2a appears to have a critical role in the proliferation of neuroblastoma cells, 41 and the ability of our system to isolate the downstream effects of HIF-2a from HIF-1a could provide further insights into this observation, as well as into the mechanisms of maintenance of endogenous NSCs. In addition to our finding of efficient neural conversion and tri-lineage differentiation we also observed that 3% O 2 allowed long-term maintenance of healthy, mixed differentiated cultures for over 3 months, in the absence of any exogenous neurotrophins that are typically required in cultures differentiated at 20% O 2 for considerably shorter periods such as to 28 days.…”
Section: Discussionmentioning
confidence: 99%